ANALISIS BAURAN PEMASARAN DI HOTEL PANGERAN BEACH PADANG - Nurmala Widyastuti (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Abstract. Based on this study to analyze the marketing mix at the Pangeran Beach Hotel Padang. This type of research is a qualitative descripptive. Determination of informants using purposive sampling technique that is many as eight research informants consisting of hotel marketing and hotel consumers. The results obtained from this study are as follows : 1) The products offered by the Pangeran Beach Hotel Padang are quality attractive and of high quality and the service provide to guests are good, 2) The Price set by the Pangeran Beach Hotel Padang is quite high and is only affordable for middle and upper class people, 3) Promotions carried out by the Pangeran Beach Hotel Padang have been maximized so that guests are still intererted in staying at the hotel, 4) The Place or location of the Pangeran Beach Hotel Padang is already strategic annd in the city center, and works together to travel agents so that guests know the location of the Pangeran Beach Hotel Padang. Keywords : Marketing, Marketing mix